L’image contre l’œuvre d’art, tout contre - Thomas Golsenne (L'Atelier du CRH)
Many years have past since art history has witnessed the emergence of a new field of research: the anthropology of images. The word “image” seems more historically and anthropologically appropriate than “art,” a term too closely defined by the more recent history of Western culture. The first goal of this paper is to compare the anthropology of images and other disciplinary fields that refute the question of “art” per se, namely visual studies and iconology. In all of these cases, the image is conceived of as representation bearing meaning, but these studies have not much to say about production or creation. Finally, we will try to establish the foundations of another approach to the study of visual objects, based on the methods of anthropology. In addition, we will consider Deleuze’s philosophy of event, in which the image is studied less as representation, and more as an as expression.